Effects of adding atracurium to Lidocaine solution during intravenous regional anesthesia in dogs - Marwa Abass; Alshimaa M. Farag; Reham A. Fahmy (Irish Veterinary Journal)
Abstract Background Acute pain management and the efficacy of analgesic therapies are essential in orthopedic surgery on the distal extremities of dogs’ forelimbs. This is due to the manipulation of both soft and orthopedic tissues. Therefore, this study aimed to compare the antinociceptive, akinesia, cardiovascular, and plasma-level effects of adding atracurium to intravenous regional anesthesia (IVRA) with lidocaine in dogs. Methods Fifty male Mongrel dogs weighing 15 ± 5 kg and aged 2.5 ± 0.6 years were premedicated with 0.045 mg/kg of atropine sulfate and 0.05 mg/kg of acepromazine. While under general anaesthesia, the dogs were randomly allocated into two IVRA groups (n = 25/group): the lidocaine group (LG; 3 mg/kg) and the atracurium (0.3 mg/kg) combined with the lidocaine (3 mg/kg) group (LAG). Following IVRA injections, the toe pinch response and nerve stimulation test were performed, with the contralateral limb serving as its control limb. The mean blood pressure (MAP), pulse rate (PR), respiratory rate (RR), end-tidal carbon dioxide level (EtCO2), rectal temperature, echocardiographic indices, and plasma lidocaine concentrations were measured. Results At 25, 35, 45, and 55 min post-induction, the LAG exhibited a significantly lower (P ≤ 0.01) nociception limb withdrawal reflex score indicated by an absence of the limb withdrawal reflex (score 1) than the LG, which showed a mild limb trembling (score 2). Moreover, at 30, 40, 50, and 60 min post-induction, the LAG had an absence of the carpus twitch (score 1) with a significantly deeper degree of nerve block (P ≤ 0.01) compared to the LG. There were no significant differences in the physiological parameters between groups during anesthesia time. Meanwhile, the MAP, PR, and RR were significantly higher (P ≤ 0.05) in the LG than in the LAG post-nociception stimuli and during the recovery period. After tourniquet removal, hypersalivation and muscle tremors were observed in four dogs in the LAG and one in the LG. Conclusion The use of IVRA with atracurium/lidocaine is a potentially effective IVRA agent for enhancing analgesia and akinesia in the distal extremities of dogs. However, it is important to consider the potential signs compatible with systemic toxicity that may occur, such as hypersalivation and muscle tremors, after releasing the tourniquet.